Rural History of Soviet Central Asia: Land Reform and Agricultural Change in Early Soviet Uzbekistan - Penati, Beatrice (Asian Studies E-Books Online, Collection 2025., 2025)
In the mid-1920s, Uzbekistan's countryside experienced a 'land reform', which aimed at solving rural poverty and satisfying radical fringes among peasants and Party, while sustaining agricultural output, especially for cotton. This book analyses the decision-making process underpinning the reform, its implementation, and economic and social effects. The reform must be understood against the background of the wreckage caused by war and revolution, and linked to subsequent policies of 'land organisation' and regime-sponsored 'class struggle'. Overall, this is the first comprehensive account of early Soviet policy in Central Asia's agricultural heartland, encompassing land rights, irrigation, credit, resettlement, and the co-operative system.